Architectural parameters of supraspinatus: a systematic review of cadaveric studies. (May 2015) - Sachdeva, Rohit; Busch, Angela J.; Harrison, Elizabeth L.; Bidonde, Julia; Kim, Soo Y.
Abstract : Background: Architectural parameters of skeletal muscles directly inform us on the functional capabilities of the muscle and are critical for understanding joint biomechanics. The supraspinatus is most commonly implicated with shoulder pathology. Thus, the more robust and accurate data are of the muscle, the better we can advance the treatment strategies. Objectives: To systematically review human cadaveric studies of the normal supraspinatus architecture. Methods: Electronic databases MEDLINE, EMBASE, CINAHL and SCOPUS were searched to identify articles describing the architectural parameters of the normal supraspinatus in human cadaveric specimens. The quality of the studies was evaluated using a checklist composed of eight factors. Results: Eighteen studies were included with the overall quality found to be low in 12. Only two studies calculated the detailed architecture of distinct regions of the muscle. The number and location of fibre bundles sampled was documented in five and four studies, respectively. There was a large range in the reported architectural values of the entire muscle: fibre bundle length (FBL), 2.8–11.7 cm; pennation angle (PA), 0–11.4°; muscle volume (MV), 23–37 cm 3 ; and physiological cross-sectional area (PCSA), 2.48–7.51 cm 2 . Conclusions: There is a significant variation in reported architectural values for supraspinatus with only a few studies providing the level of detail and quality suitable for advancing our understanding of shoulder biomechanics. The critical factors identified in the review may guide and improve the quality of future skeletal muscle architectural studies.